Perceived Value and Customer Satisfaction in the Nigerian Airlines Businesses - Adebayo, Adeyemi Abdulwasiu; Salau, Abdulazeez Alhaji (ASEAN Marketing Journal, 2025)
Due to the nature of consumers as being price conscious and their attitude in evaluating if the services rendered by service providers can meet their needs and aspirations, airline service providers need to understand the perceived value of their esteemed customers to ensure that the services rendered are satisfying and can ultimately lead to loyalty. This study investigated the influence of customer perceived value proxy with customer experience and service quality in building satisfaction in the Nigerian Airline business. The study employed a quantitative research design through a survey to collect primary data from domestic customers of the chosen airlines. The sample size of 246 was determined using Godden’s (2024) model, considering the nature of the population, and multistage sampling techniques were also used. 150 copies of questionnaires were finally gathered for data analysis as Standard multiple regression was employed to analyze the data. The findings indicated that customer experience showed a significant relationship with customer satisfaction and loyalty (β = .253, t = 3.502, p < .001), and service quality also exhibited a positive and significant association with customer satisfaction and loyalty (β .192, t = 2.529, p = .012). The study concluded that customer value can appreciably influence a company’s brand reputation as high customer value often enhances customer satisfaction and loyalty, which can develop in positive word-of-mouth and customer advocacy. The study recommended that airline service providers try to work on how positive customer experience can generate customer satisfaction and inevitably influence customer loyalty by using technology, customer journey mapping, and personalizing the customer offering to create breakthroughs in customer experience.